2013
DOI: 10.1007/s11030-013-9440-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary anti-proliferative activity evaluation of 1-(quinolizidin-1’-yl)methyl- and 1-( $$\omega $$ -tert-amino)alkyl-substituted 2-phenyl-, 2-benzyl- and 2-[(benzotriazol-1/2-yl)methyl]benzimidazoles on human cancer cell lines

Abstract: Twenty benzimidazole derivatives bearing in position 1 a ([Formula: see text]-tert-amino)alkyl chain (mainly quinolizidin-1-ylmethyl) and in position 2 an aromatic moiety (phenyl, benzyl or benzotriazol-1/2-ylmethyl) were evaluated at the National Cancer Institute (NCI) for anti-proliferative activity against a panel of 60 human cancer cell lines. Four compounds (6, 7, 9 and 10) displayed a large spectrum of activity with [Formula: see text] 10 [Formula: see text] on 24-57 cell lines, while thirteen compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Anticancer studies using several classes of polyaromatic antitumour agents indicate that the introduction of a nitrogen-containing side chain increases significantly the biological activity and potency of the parent compounds. For example, it has been shown that the presence of the nitrogen moiety in flavopiridol, a synthetic nitrogen-containing flavonoid with antitumor activity against various tumor cell lines, is critical for its antitumor effect [ 9 ]. The Mannich reaction is a commonly used way to introduce nitrogenous moieties, such as aminoalkyl group to phenols.…”
Section: Introductionmentioning
confidence: 99%
“…Anticancer studies using several classes of polyaromatic antitumour agents indicate that the introduction of a nitrogen-containing side chain increases significantly the biological activity and potency of the parent compounds. For example, it has been shown that the presence of the nitrogen moiety in flavopiridol, a synthetic nitrogen-containing flavonoid with antitumor activity against various tumor cell lines, is critical for its antitumor effect [ 9 ]. The Mannich reaction is a commonly used way to introduce nitrogenous moieties, such as aminoalkyl group to phenols.…”
Section: Introductionmentioning
confidence: 99%
“…Screening test of caspase‐dependent apoptosis showed 68 and 69 to be more potent than tirapazamine upon exposure to A549 cell. Other recently established anticancer benzimidazoles are 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , and 78 (Fig. ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…During the last few years, our research group developed a large variety of benzimidazole derivatives with different pharmacological aims, in particular, exploring the analgesic, 18 antiviral [19][20][21] and anti-tumor 22 activities. Our benzimidazoles, studied in vivo as analgesic drugs, were designed on the basis of previous work of CIBA (now Novartis), that led to etonitazene, the most potent μ-opioid currently known.…”
Section: Introductionmentioning
confidence: 99%